2013
DOI: 10.4161/rna.26562
|View full text |Cite
|
Sign up to set email alerts
|

Length variants of the 5′ untranslated region of p53 mRNA and their impact on the efficiency of translation initiation of p53 and its N-truncated isoform ΔNp53

Abstract: Recently, we have determined the secondary structure of the 5'-terminal region of p53 mRNA that starts from the P1 transcription initiation site and includes two major translation initiation codons responsible for the synthesis of p53 and ΔNp53 isoform. Here, we showed that when this region was extended into 5' direction to the P0 transcription start site, the two characteristic hairpin motifs found in this region were preserved. Moreover, the presence of alternatively spliced intron 2 did not interfere with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 48 publications
7
42
0
Order By: Relevance
“…Translation of proteins with alternative initiation codons may take place by re-initiation, by leaky scanning by the ribosome or by the IRES: all these possibilities have been discussed with regard to the synthesis of Δ40p53 (Błaszczyk & Ciesiołka, 2011). Importantly, it has been demonstrated that the longer 5' terminus of p53 mRNA strongly reduces the synthesis of the p53 and Δ40p53 proteins (Górska et al, 2013). This is consistent with the observations that the longer 5'UTR results in lower productivity of the cap-dependent translation system (Vassilenko et al, 2011).…”
Section: Regulation Of the P53 Translation Initiationsupporting
confidence: 85%
See 4 more Smart Citations
“…Translation of proteins with alternative initiation codons may take place by re-initiation, by leaky scanning by the ribosome or by the IRES: all these possibilities have been discussed with regard to the synthesis of Δ40p53 (Błaszczyk & Ciesiołka, 2011). Importantly, it has been demonstrated that the longer 5' terminus of p53 mRNA strongly reduces the synthesis of the p53 and Δ40p53 proteins (Górska et al, 2013). This is consistent with the observations that the longer 5'UTR results in lower productivity of the cap-dependent translation system (Vassilenko et al, 2011).…”
Section: Regulation Of the P53 Translation Initiationsupporting
confidence: 85%
“…Additionally, it has been demonstrated that the coding sequence is necessary for proper folding of the 5' terminus of the P1-initiated transcript (Błaszczyk & Ciesiołka, 2011). In the P0-initiated p53 mRNA three small hairpins were identified in the P0-P1 region (Górska et al, 2013). In vitro and in vivo experiments have shown that the P0-P1 region influences p53 translation efficiency (Strudwick et al, 2003;Górska et al, 2013).…”
Section: Human P53 Mrna Transcripts and P53 Isoformsmentioning
confidence: 99%
See 3 more Smart Citations